In vitro Toxico-genomics of Etoposide Loaded Gelatin Nanoparticles and Its in-vivo Therapeutic Potential: Pharmacokinetics, Biodistribution and Tumor Regression in Ehrlich Ascites Carcinoma (EAC) Mice Model - Moin, Imran; Biswas, Largee; Zafaryab, Md; Kumari, Namrata; Leekha, Ankita; Mittal, Disha; Verma, Anita Kamra (Frontiers in Nanotechnology, 2021)
Globally, breast cancer is the foremost cause of mortality among women detected with cancer, with 21% diagnosed in India alone. Etoposide loaded gelatin nanoparticles (EGNP) were prepared and its physical characterization (size:150nm±0.241; zeta potential -29.32 mV) was done along with in-vitro studies to assess biotoxicity, intracellular ROS, cell cycle arrest and death caused by EGNPs. We report the molecular pathways induced by EGNP in-vitro, pharmacokinetics, biodistribution and tumor regression in-vivo in Balb/c mice. Gene expression profiling of Bax, BCL2, p53, Caspase-3, RIPK1, RIPK3 and β-actin as internal control were done by RT-PCR wherein Etoposide and EGNP treated MCF-7 cells showed higher expressions of apoptotic genes-Bax, p53, caspase-3, lower expression of anti-apoptotic gene-Bcl2 when compared to control. Enhanced expression of necroptosis-RIPK1 were observed, while RIPK3 was insignificant. Since, RIPK1 regulates necroptosis and apoptosis, expression of apoptotic markers confirmed apoptotic molecular mechanisms. Negligible hemolysis of Gelatin nanoparticles (GNP), and EGNP at selected dosages confirmed biocompatibility. In vivo pharmacokinetics and biodistribution were done by 99Tc-labelled nanoparticles indicating increased circulation of EGNPs, allowing accumulation at the tumor site by Enhanced permeability and retention (EPR) phenomena. Tumor regression indicates the efficacy of EGNP by reducing the tumor burden when compared to void GNP and Etop per se, resulting in increased life span. High biocompatibility and bio-efficacy of EGNPs prove their therapeutic potential in cancer treatment.